2019
DOI: 10.3389/fonc.2019.00510
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and Targeted Therapy for Hormone-Receptor-Positive, HER2-Negative Advanced Breast Cancer: Insights to Sequencing Treatment and Overcoming Resistance Based on Clinical Trials

Abstract: Background: Advanced hormone-receptor positive HER2 negative breast cancer is a common and a very heterogeneous disease. Hormone therapy is the main first line treatment of choice, given alone or in combination with other agents that have shown to improve patient outcomes, Nevertheless, treatment remains generally palliative rather than curative. Sequencing of such treatment remains challenging, especially with resurgence of variable resistance patterns. Multiple attempts have been made to overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 153 publications
(153 reference statements)
0
39
0
1
Order By: Relevance
“…Breast cancer remains the most common malignancy and cause of cancer-associated death amongst women worldwide [1,2]. For patients with metastatic breast cancer (MBC) the disease is almost always fatal, with 5-year survival rates of approximately 26% [3,4]. In early-stage breast cancer, treatment decisions are guided by the clinical subtypes of oestrogen receptor positive (ER+ HER2−), human epidermal growth factor receptor 2 amplified (HER2+) and triple-negative breast cancer (TNBC), which are defined by the presence or absence of the oestrogen receptor and progesterone receptor and HER2 overexpression or gene amplification.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer remains the most common malignancy and cause of cancer-associated death amongst women worldwide [1,2]. For patients with metastatic breast cancer (MBC) the disease is almost always fatal, with 5-year survival rates of approximately 26% [3,4]. In early-stage breast cancer, treatment decisions are guided by the clinical subtypes of oestrogen receptor positive (ER+ HER2−), human epidermal growth factor receptor 2 amplified (HER2+) and triple-negative breast cancer (TNBC), which are defined by the presence or absence of the oestrogen receptor and progesterone receptor and HER2 overexpression or gene amplification.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the agonist effect of tamoxifen may induce a risk of endometrial cancer after long-term use in postmenopausal women [71]. Generally, AIs and fulvestrant are used to follow or replace when patients are resistant to tamoxifen [71,72]. However, resistance to AIs and fulvestrant eventually occurs [73][74][75].…”
Section: Endocrine Resistancementioning
confidence: 99%
“…Recently, multiple targeted agents are used to overcome endocrine resistance, including the use of inhibitors for cyclin-dependent kinases 4 and 6 (CDK4/6), mammalian target of rapamycin (mTOR), PI3K/AKT and histone deacetylase, as well as investigation of new SERDs/SERMs [70,72,80]. In addition, it has been shown that HER2 inhibitors combined with endocrine therapies contain clinical benefit [79].…”
Section: Endocrine Resistancementioning
confidence: 99%
“…2,6,22,23 Adding a targeted therapy to ET has been shown to improve efficacy and delay the development of endocrine resistance. 6,22,23 Targeted therapies include CDK4/6 inhibitors (ribociclib, palbociclib and abemaciclib), the mTOR inhibitor everolimus and the phosphatidylinositol 3-kinase (PI3K) inhibitor alpelisib (approved for use in combination with fulvestrant as a treatment for postmenopausal women and men with HR + /HER2 -, PIK3CAmutated metastatic breast cancer, after progression on or after an endocrine-based regimen). 6,23,24 The development of potent, selective, orally bioavailable CDK4/6 inhibitors has transformed the care of patients with advanced HR + /HER2breast cancer.…”
Section: First-line Therapy For Advanced Hr + /Her2breast Cancermentioning
confidence: 99%
“…6,22,23 Targeted therapies include CDK4/6 inhibitors (ribociclib, palbociclib and abemaciclib), the mTOR inhibitor everolimus and the phosphatidylinositol 3-kinase (PI3K) inhibitor alpelisib (approved for use in combination with fulvestrant as a treatment for postmenopausal women and men with HR + /HER2 -, PIK3CAmutated metastatic breast cancer, after progression on or after an endocrine-based regimen). 6,23,24 The development of potent, selective, orally bioavailable CDK4/6 inhibitors has transformed the care of patients with advanced HR + /HER2breast cancer. 6,25,26 Each of the available CDK4/6 inhibitors -ribociclib, palbociclib and abemaciclib -has been shown to be effective and generally well tolerated when used in combination with ET in both the first-line [25][26][27][28][29][30][31][32][33][34] and second-line settings.…”
Section: First-line Therapy For Advanced Hr + /Her2breast Cancermentioning
confidence: 99%